INTERAKSI YESUS DENGAN PETRUS DALAM INJIL MATIUS 16:21-28 SEBAGAI MODEL PENANGANAN MASALAH KEJIWAAN: THE INTERACTION OF JESUS WITH PETRUS IN THE GOSPEL OF MATTHEW 16: 21-28 AS A MODEL FOR HANDLING OF PSYCHIATRIC PROBLEMS - Silwanus Gabriel (Jurnal Teologi Amreta (ISSN: 2599-3100))
The author argues that the Pentecostal ministry that is in contact with the handling of psychiatric problems (PMK) can use the story of Jesus' interaction with Peter in Matthew 16: 21-28 as his foundation. Indeed, the story was not originally intended to talk about PMK at all, but when read using Christian psychological theory, it will be able to emerge from the basic principles of PMK. Jesus' interaction with Peter in Matthew 16: 21-28 also displays cognitive-behavioral aspects. Matthew expertly narrated the way Jesus used to give Peter a kind of therapy. Matthew records this event more fully than Mark and Luke. It is the completeness of these records that makes Matthew's writing suitable for use as a PMK model. For this purpose, a study of parallelism, background searches and culture will be used to discover Matthew's unique presentation compared to the other two Gospels. Next, Matthew's presentation of Peter's words and actions to Jesus and Jesus' response to those words and actions will be analyzed using cognitive behavioral therapy. In the end, the results of this study will be viewed from the Pentecostal side as a PMK model. === Penulis berargumen bahwa pelayanan Pentakosta yang bersentuhan dengan penanganan masalah kejiwaan (PMK) dapat menggunakan kisah interaksi Yesus dengan Petrus dalam Matius 16:21-28 sebagai dasar pijakannya. Memang kisah itu pada mulanya tidak dimaksudkan sama sekali untuk berbicara tentang PMK, tetapi ketika dibaca dengan menggunakan teori psikologi Kristen, maka dari dalamnya akan dapat dimunculkan prinsip-prinsip dasar PMK. Interaksi Yesus dengan Petrus dalam Matius 16:21-28 juga menampilkan aspek cognitive-behavioural. Dengan piawai Matius menarasikan cara yang digunakan Yesus untuk memberikan semacam terapi kepada Petrus. Matius mencatat peristiwa ini dengan lebih lengkap dibandingkan dengan catatan Markus dan Lukas. Kelengkapan catatan inilah yang membuat Tulisan Matius cocok digunakan sebagai model PMK. Untuk tujuan ini, telaah paralelisme, penelusuran latar belakang dan budaya akan digunakan untuk menemukan keunikan presentasi Matius dibandingkan kedua Injil yang lain. Berikutnya, presentasi Matius tentang perkataan dan tindakan Petrus kepada Yesus dan tanggapan Yesus terhadap perkataan dan tindakan itu akan dianalisa dengan menggunakan terapi cognitive behavioral. Pada akhirnya, hasil telaah ini akan dilihat dari sisi Pentakosta sebagai sebuah model PMK.